2014
DOI: 10.1590/s0102-86502014001700004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ischemic preconditioning and cilostazol on muscle ischemia-reperfusion injury in rats

Abstract: PURPOSE:To evaluate effects of ischemic preconditioning and Cilostazol on muscle ischemia-reperfusion injury. METHODS:Male Wistar rats were submitted to muscle ischemic and reperfusion injury (4h of the left common iliac artery occlusion followed by 1h of reperfusion). Five experimental groups were constituted: Control group (n=4); Ischemia-Reperfusion (IR, n=5); Ischemic preconditioning group (IP, n=6); Ischemia-Reperfusion group treated with cilostazol (IRCi, n=6) and Ischemic preconditioning group treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Santos et al, investigating the protective effect of cilostazol on isolated rabbit femoral arteries, claimed that cilostazol has improved vascular reactivity after revascularization [ 5 ] . However, Neto et al found no beneficial effect of cilostazol on kidney and skeletal striated muscle in rats with IRI models [ 6 ] . In contrast, O’Donnell et al found positive effects of cilostazol on exercise-induced IRI in 90 patients with peripheral artery disease [ 7 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Santos et al, investigating the protective effect of cilostazol on isolated rabbit femoral arteries, claimed that cilostazol has improved vascular reactivity after revascularization [ 5 ] . However, Neto et al found no beneficial effect of cilostazol on kidney and skeletal striated muscle in rats with IRI models [ 6 ] . In contrast, O’Donnell et al found positive effects of cilostazol on exercise-induced IRI in 90 patients with peripheral artery disease [ 7 ] .…”
Section: Introductionmentioning
confidence: 99%
“…The histopathological evaluation of rat kidney and heart was done by two experienced histopathologists. For the quantification of the tissue damage, a scoring system was employed based on previously published criteria [14][15][16][17] . Collective histological scoring ranged from 0 (within normal range) to 5 (severe organ injury).…”
mentioning
confidence: 99%